(untitled) (Biological Sciences - PJSIR, 1998)
An experiment was conducted in cemented tanks with four wheat genotypes: two were tolerant (Chakwal-86 and AZS-4) and two susceptible (Pavon and AZS-17) to water stress. The parameters estimated were the photosynthetic efficiency andnitrogenmetabolismofthegentoypes. Measurementsweremadeofaccumulation ofdrymatter,transpi- ration, leafdiffusive resistance, leaf area,nitratereductase activity (NRA) and total amino acids. Results showed that leafarea,transpiration, drymatteraccumulationandNRAwerereducedwhiIeleafdiffusive resistanceandtotalamino acids increased in all the genotypes under all stress treatments. The relationship between yield and leaf area, transpiration, dry matter accumulation andNRA waspositive. The genotypes Chakwal-86 and AZS-4 showed betier performance than theothers.